2017
DOI: 10.1212/wnl.0000000000003788
|View full text |Cite
|
Sign up to set email alerts
|

Cervical artery dissection in patients ≥60 years

Abstract: In our study population of patients diagnosed with CeAD, 1 in 14 was aged ≥60 years. In these patients, pain and mechanical triggers might be missing, rendering the diagnosis more challenging and increasing the risk of missed CeAD diagnosis in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Especially younger people (< 45 years) seem to have an increased risk to develop a craniocervical artery dissection, as opposed to older people with multiple cardiovascular risk factors for atherosclerosis (Cassidy et al, 2008(Cassidy et al, , 2017Goeggel Simonetti et al, 2015;Kranenburg et al, 2017;Rothwell et al, 2001;Rubinstein et al, 2005;Schievink, 2001;Traenka et al, 2017). A review of 134 case reports of serious adverse events after cervical spine manipulation showed that the mean age of these people was 44 (range 23-86) years, and only 26.1% were older than 50 years (Puentedura et al, 2012).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially younger people (< 45 years) seem to have an increased risk to develop a craniocervical artery dissection, as opposed to older people with multiple cardiovascular risk factors for atherosclerosis (Cassidy et al, 2008(Cassidy et al, , 2017Goeggel Simonetti et al, 2015;Kranenburg et al, 2017;Rothwell et al, 2001;Rubinstein et al, 2005;Schievink, 2001;Traenka et al, 2017). A review of 134 case reports of serious adverse events after cervical spine manipulation showed that the mean age of these people was 44 (range 23-86) years, and only 26.1% were older than 50 years (Puentedura et al, 2012).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Severe, unusual headache or neck pain are often the first symptoms of an underlying craniocervical artery dissection (Debette and Leys, 2009;Taylor and Kerry, 2010). In patients older than 60 years, pain and mechanical triggers might be missing because cervical pain is not a hallmark of craniocervical artery dissection in patients older than 60 years (Traenka et al, 2017). Interpreting data from the patient interview and defining the main hypothesis is essential for an effective physical examination (Petty, 2011;Rushton and Lindsay, 2010).…”
Section: The Patient Interviewmentioning
confidence: 99%
“…The average age of patients is 40 years,15 with only 7% of patients aged ≥60 years 16. Men are affected more than women 17.…”
Section: Discussionmentioning
confidence: 99%
“…16 A more indolent course and non-localised pain does not, however, exclude this diagnosis; in particular, carotid dissection can present without initial neurological deficits. [17][18][19] Acute-onset limb weakness suggests stroke. Weakness in the case of stroke involves more than one myotome, with extension weakness in the upper limb and flexion weakness in the lower limb predominating.…”
Section: Infectionmentioning
confidence: 99%
“…• Vascular emergencies -Sudden onset tearing nature, recurrent thunderclap headache, unilateral weakness, vertigo [16][17][18][19] • Myocardial ischemia -Typically associated with other cardiac features 21…”
Section: Infectionmentioning
confidence: 99%